Kurdish Sorani Natural Language Processing Text Classification Using Different Machine Learning Algorithms - Mhamad Amin, Orme; Abdulqadir Ali, Nzar (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Researchers assessed machine learning models on Kurdish Sorani natural language progression classification utilizing dataset information obtained from different Kurdish news sites. The collected dataset contains five categories which are business, sport, health, social and technology. The research tested Extreme Gradient Boosting (XGBoost) as well as Random Forest (RF) alongside Support Vector Machine (SVM) algorithms and Light Gradient Boosting Machine (LGBM). The results show that (SVM) prove the most effective performance reaching the maximum accuracy and F1-scores across all classification categories. Although XGBoost displayed good performance in classifying technology and culture news Random Forest and LGBM struggled to realize accurate outcomes for the social class category. The study highlights the potential of modern machine learning models for attractive text classification tasks.